2017
DOI: 10.1103/physrevapplied.7.034005
|View full text |Cite
|
Sign up to set email alerts
|

Gain-Based Mechanism for pH Sensing Based on Random Lasing

Abstract: Here, we investigate the mechanism of a random-lasing-based sensor which shows pH sensitivity exceeding by 2 orders of magnitude that of a conventional fluorescence sensor. We explain the sensing mechanism as related to gain modifications and lasing-threshold nonlinearities. A dispersive diffusive lasing theory matches the experimental results well, and it allows us to predict the optimal sensing conditions and a maximal sensitivity as large as 200 times that of an identical fluorescence-based sensor. The lack… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…As the diameter of voids is decreased, the ASE threshold tends to decrease and the number of RL spots increases, indicating that random cavities with high-Q factors arise because of the shortened scatterers. It is noteworthy that we observed no RL behavior at the 1-μm SIO for which refs 24,25 reported gain enhancement, but RLs were obtained even when the diameter was reduced to 100 nm (Supplementary Fig. 5).…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…As the diameter of voids is decreased, the ASE threshold tends to decrease and the number of RL spots increases, indicating that random cavities with high-Q factors arise because of the shortened scatterers. It is noteworthy that we observed no RL behavior at the 1-μm SIO for which refs 24,25 reported gain enhancement, but RLs were obtained even when the diameter was reduced to 100 nm (Supplementary Fig. 5).…”
Section: Resultsmentioning
confidence: 59%
“…The third harmonic of a pulsed neodymium-doped yttrium aluminum garnet (Nd:YAG) laser at 355 nm (pulse duration of 25 ps and repetition ratio of 2 Hz) pumped the dye-doped silk film and the SIO to exhibit ASE and RL. In refs 24,25 , the authors claim that the spectra were obtained from similar structures to our SIO show RL and that they engineered the first silk-based biocompatible RL However, the narrowed spectral peak above threshold with about 10-nm full width at half maximum (FWHM) just indicated the transition to the ASE from the photoluminescence (PL, the fluorescence of a dye). Further, we confirmed that our bulk silk/dye film with no micro/nanostructures exhibited the same spectral behaviors as those reported in refs 24,25 .…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The spectral characteristics of the laser emission are strongly dependent on the scattering properties of the medium, providing new tools to investigate disordered biological materials. To date, random lasers have shown the feasibility to detect physical changes or chemical changes within biological materials . Figure a shows the sensing mechanism of a random laser, by using pH sensing as an example.…”
Section: Biological and Biomedical Sensingmentioning
confidence: 99%
“…Narrow linewidth (lasing) is observed when the pH value is neutral, while broad fluorescence emission is observed when it has alkaline pH values. Adapted with permission . Copyright 2017, American Physical Society.…”
Section: Biological and Biomedical Sensingmentioning
confidence: 99%